Project-driven technology strategy : knowledge--technology - McGrath, Robert N. (Project Management Institute, 2012)
In today's enterprise, technology isn't about software or hardware. It's about knowledge and competence. And it's the key to creating a sustained competitive advantage for your organization. Dr. Robert McGrath's new book not only redefines technology but reshapes how to approach the age-old challenges of fostering innovation, growing entrepreneurship and creating value. Described as a combination of ""a master class taught by your most thought-provoking professor"" and ""a troubleshooting session with your most trusted mentor"", this groundbreaking work uses classic economic theory from luminar